(untitled) (Revista Argentina de Musicología, 2012)
We document the creation and the initial critical reception of the activity of the Symphonic Band of Buenos Aires, an institution whose work begins in 1910 and continues to the present day. Conceived ‘in a large scale’ (a symbolic hundred of musicians, a renowned baton and a inaugural concert that took place in the most legitimist theater of the whole Argentina), the Municipal Band of Buenos Aires seems to have assumed an important role in the joyful rhetoric of the Centenary of the May Revolution. Associated with the generalized enthusiasm and to the novelty of its instrumental conformation and repertoire, performances of the Band meant for the citizens of Buenos Aires something more than sparkling soirée series. The figure of the conductor, Antonino Malvagni, played in favor of the rate of the institution. Likewise, the multitude of the heterogeneous population conformed by immigrants, summed to diverse types of identifications, and delineated an incipient ‘national’ identification. During the times of ‘bicentenaries’, reflections about some historic processes that the “centenaries’ originated as ‘landmarks’ symbolically productive of evocation, balance and projection, attempt a contribution to a socio-cultural history of music of (and in) Argentina.